Menyoal Efektifitas Kuliah Daring: Analisis Filosofis atas Dinamika Kuliah Daring Selama Pandemi Covid-19 dalam Terang Pemikiran Jean-Jacques Rousseau - Kristoforus Garnodin; Sebastianus Hagoldin (Parahyangan Catholic University, 2021)
The focal point of the discussion of this research is the relevance of Jean-Jacques Rousseau’s thoughts to online lectures. The basic concept of education according to Rous- seau lies in forming free, independent human beings without pressure or bondage, not for a particular purpose. In other words, freedom is the basic law of education. The covid-19 pandemic has forced lectures to be conducted online. The change in the lecture system from face-to-face to a new system, namely online, has become a reality that is not easy to implement. There are many challenges that occur both from the educational institutions, teaching staff, and students. This happens because lecturers and students themselves do not have a balanced ability to provide or receive lecture material online. The method used in this paper is to analyze the thoughts of the characters in the context of online lectures. This study found that the dynamics of lectures that occurred during the covid-19 pandemic did not work effectively. The teaching staff has not been able to fully provide lecture mate- rial to the maximum and students also cannot absorb the material optimally.